INDONESIA TO HOST THE FIFA WORLD CUP? A COST-BENEFIT ANALYSIS - Pohan, Hilda Masniaritta; Oktavianty, Silvy Puspita (Penerbit Atma Jaya Catholic University of Indonesia, 2018)
Numerous studies have shown that hosting the FIFA World Cup potentially creates positive economic benefits although it costs a substantial amount of money. The biggest cost comes from infrastructure needs which are highly correlated with a country’s geographical characteristics. This research evaluates the feasibility of hosting the FIFA World Cup in Indonesia given its geographical characteristics. Using data compiled from various studies, estimation was conducted using Cost-Benefit Analysis. Results show that hosting the FIFA World Cup is not financially profitable for Indonesia. However, after accounting for potential social benefits, economic analysis suggested that in the short run, it potentially boosts tourism and income of related sectors. In the long run, benefits include acquiring top notch stadiums, provision of high quality infrastructure, training opportunities for talented young players, and exposure of Indonesia’s tourist attractions. These social benefits may outweigh the financial loss; making the hosting project economically viable.